Self Correction in Translation Courses: A Methodological Tool - Mizón M., M.; Diéguez M., M. (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe article has three basic objectives: 1) to provide a psycholinguistic grounding of pedagogical procedures in the didactics of translation, specifically for the technique of self-correction, 2) to provide concrete examples of self-correction and discuss them in light of this theoretical background, and 3) to suggest practical implications of this technique in the field of translator training.